Análise da influência da ocupação do solo na variação da temperatura em diferentes localidades da cidade de Curitiba - Rossi, Francine Aidie (2004)
Urban climate has been modified by human activities. In this way, urbanization brings direct and indirect influences to climate characteristics of a given location. One of the factors that can contribute directly to the creation of urban climate is land use. The present research investigated how land use can influence temperature variations in Curitiba. Thus, 14 different locations of Curitiba were analyzed during a 1-month period by monitoring air temperature and humidity as well as quantifying land use patterns for each location. The monitoring of climatic data occurred in winter (June/July) and was carried out for two years, 2002 and 2003. Reference baseline was SIMEPAR meteorological station, which was used for comparisons. Comparisons were made regarding averages of the minimum, average and maximum temperatures for each location and the difference between each location to the reference station. For the land use analysis, five categories of land use were selected (water area, built area, free area, paved area and green area) and quantified as percentages for three areas of influence. Linear regression analysis was made, a comparative analysis between air temperature data and land use patterns, analysis of spatial distribution of temperature and thermal comfort analysis for each location. The main objective was to indicate an excellent ratio between the five land use categories considered, in order to offer more adequate temperature variation in terms of thermal comfort.